Pemanfaatan Data Lidar untuk Pembuatan Digital Terrain Model (DTM) dan Analisis Slope pada Perencanaan Pembangunan Villa - Puja Kharisma; Fajrin Fajrin; Defwaldi Defwaldi; Ilham Armi (Jurnal Sains dan Ilmu Terapan, 2026)
Planning villa development in complex topographic areas requires accurate and detailed terrain information to ensure safety, construction efficiency, and environmental sustainability. This study aims to utilize LiDAR data to generate a Digital Terrain Model (DTM) and conduct slope analysis to support villa development planning in Budo Village, Wori District, North Minahasa Regency. The research employed a quantitative applied approach using LiDAR point cloud data processed through classification, filtering, and interpolation to produce a DTM, followed by slope analysis using GIS. The results show that the study area has elevation variations between ±73 and ±173 meters above sea level with a vertical RMSE accuracy of 0.487 meters, classified as very good. Slope classification indicates that flat (0–8%) and gentle (8–15%) areas dominate the central region and are highly suitable for villa development due to low geotechnical risk and minimal earthwork requirements.